RESERVOIR POTENTIAL OF THE SYN-RIFT SUCCESSION IN NORTHWEST PALAWAN, PHILIPPINES - Tuazon Vinarao, Charlotte (Bulletin of Earth Sciences of Thailand, 2021)
This study focused on identifying depositional environments and their corresponding sedimentary facies to understand implications for reservoir potential in the NW Palawan Basin, Philippines. Rock physics relationships, well-based facies analysis, seismic facies analysis and mapping of depositional sequences identified sedimentary facies deposited as a result of interplay between different depositional settings. Depositional processes were controlled by tectonic activity, relative sea level change, subsidence and sedimentation. The facies change from an alluvial fan on the bounding fault margin that grade into marine facies in the basin axis and to a delta prograding into the basin from the flexural margin. Sedimentary facies change across the graben and reservoir distribution is limited by depositional setting. Reservoir quality in the Malajon-1 well was affected by both compaction and cementation to varying degrees. Potential hydrocarbon-bearing reservoirs of significant thickness and lateral extent were not penetrated by the Malajon-1 well. Reservoirs that appear to be more prospective are found mainly in channels and in deltas.